Synthesis of dipyrrolic species for direct preparation of mesosubstituted chlorines - N. V. Konovalova; O. V. Motova (Тонкие химические технологии, 2008)
A dipyrrolic structures were synthesised for direct preparation of asymmetrically functionalized chlorin macrocycles